2018
DOI: 10.1002/cctc.201801146
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photo‐Reduction of p‐Nitrophenol by Protonated Graphitic Carbon Nitride Nanosheets

Abstract: Photocatalytic reduction of p‐nitrophenol to p‐aminophenol is important because of the high toxicity of p‐nitrophenol and the wide application of p‐aminophenol. Graphitic carbon nitride (g‐CN) is an excellent photocatalyst for various photo‐reduction reactions, but inefficient for photo‐reduction of p‐nitrophenol due to the electrostatic exclusion. In this work, we control the morphology and surface property of g‐CN and achieve significantly enhanced activity. The obtained protonated g‐CN nanosheet (pg‐CNNS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 63 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…For Ag/KNbO 3 composite it generates a photocurrent of 1.5 μA/cm 2 under visible light, which confirms the existence of the photosensitization effect of Ag NPs. The highest photocurrent is obtained under UV light irradiation, indicating its best efficiency in charge separation. Meanwhile, it confirms the negative effect of the photosensitization effect. The result in Figure agrees well with the data in Figure , confirming the rationality of the proposed mechanism in Figure .…”
Section: Results and Discussionmentioning
confidence: 77%
“…For Ag/KNbO 3 composite it generates a photocurrent of 1.5 μA/cm 2 under visible light, which confirms the existence of the photosensitization effect of Ag NPs. The highest photocurrent is obtained under UV light irradiation, indicating its best efficiency in charge separation. Meanwhile, it confirms the negative effect of the photosensitization effect. The result in Figure agrees well with the data in Figure , confirming the rationality of the proposed mechanism in Figure .…”
Section: Results and Discussionmentioning
confidence: 77%
“…In addition, it is obvious that the reaction rate of the 1T/2H-MoS 2 is much higher than the 2H-MoS 2 , that the degradation percentage is 5.4 times that of the 2H-MoS 2 . According to the former research studies, 21,22,33 the 4-NP degradation to 4-AP follows 4 steps, as shown in Figure S3. To confirm the mechanism and further investigate the promotion from the 1T/2H hybrid phase, a series of CV tests were carried out in pH = 6 PBS buffer solution containing 2 mM of 4-NP (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Comparing with 4-NP, 4-AP could be a useful candidate in analgesic, antipyretic drugs, or corrosion inhibitor fields. 21,22 Light-assisted 4-NP to 4-AP has been reported by various photocatalysts, such as TiO 2 , CdS, etc. 20,23,24 In contrast, the 4-NP can be reduced more easily by catalysts containing noble metallic nanoparticles (such as Au or Ag).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, ammonia was added to the above mixture till the pH reached 7 and it was allowed to stir for 30 min. The addition of H 2 SO 4 into g-C 3 N 4 NS helps in exfoliation of nanosheets, by bearing the positive charges and is further neutralized by adding ammonia [33,40]. The final product was centrifuged, washed and dried.…”
Section: Preparation Of G-c 3 N 4 /Tiomentioning
confidence: 99%